Systematic review and classification of: Glennes Parent Programme: A Guidance Programme for Parents of Children with Autism Spectrum Disorders - Halvorsen, Marianne Berg; Kaiser, Sabine (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2025)
Background: This is a systematic review of the effect of Glennes parent program for parents of school-age children or adolescents with autism spectrum disorder. The parent program is based on the program "The Incredible Years" and applied behavioral analysis, where autism-specific adaptations have been made in the understanding of what can trigger, reinforce and maintain behavioral problems in parent-child interactions. This is a manual-based group intervention where parents participate over twelve weekly sessions. In addition, a rehearsal session is also offered. The overall aim is to strengthen positive interaction between parents and children to prevent behavioral problems. The intervention is developed by and owned by Glenne Regional Center for Autism at Vestfold Hospital, which provides training and supervision for the program's group leaders.Method: This review is based on a systematic literature search in the databases Embase, Medline, and PsycINFO, NORART, Cochrane, Cristin, NORA, SCOPUS, and SweMed. Evidence was also sought in international evidence databases, and information about the intervention was obtained from the intervention owner. The literature search and other gathered information were reviewed to identify Nordic efficacy studies, international summary studies, and any other Norwegian studies on the intervention.Results: The intervention is well described in the manual and other materials and has a good theoretical justification. It has overall good implementation quality but lacks specification of how compliance with core components of the intervention can be ensured. The literature search identified 13 articles. Four of these were included and categorized as “other Norwegian” studies as they were not of the research methodological quality to evaluate them as effect studies.Conclusion: There is no study of sufficient high methodological quality to assess whether the intervention is effective. Good theoretical foundation supports that the intervention may be effective, but this must be investigated in future effect studies.Glennes parenting program is classified at evidence level 2 - Theoretically justified intervention.
Keywords: Systematic review; Autism Spectrum Disorders; parent guidance program; Group-Based Intervention